Factors Affecting Treatment Seeking Patterns amongst Public in Three Selected Areas in Kuantan: Discovery of perceptions (dzan) among community as thought in Islam - Yusof, Afzan Mat; Ahmad Arifin, Syamsul; Md Isa, Lokman (IIUM Medical Journal Malaysia, 2018)
Seeking treatment is a vital when an individual falls sick. However, some may not do so perhaps they are ashamed to admitting having shameful diseases or unable to seek and reach help. Negative perception of the community on sensitive diseases like AIDS or sexual transmitted disease (STD) may drive the patients away from seeking treatment and suffer alone. In Islam we are thought to always have positive perceptions (husnu dzan) towards any issues in daily life especially when dealing with human interaction by avoiding bad perceptions (su’u dzan). Thus, this study aims to identify the factors affecting treatment seeking patterns among public in three selected areas in Kuantan, and to explore factors affecting people not able or avoid seeking treatment, also to determine the relationship between treatment seeking patterns and the influential factors ie distance, accessibility and behaviour; attitude to health, healthcare and selfperception. A cross sectional survey was carried out at Taman Gelora, Teluk Cempedak and Terminal Makmur, Kuantan, Pahang. Convenient sampling method was used in this study. 201 respondents participated and answered a semi-structured questionnaire modified from Adamson. Results showed that the data was normally distributed, 50.2% respondents were male and 58.7% the total respondents were between 16-26 years old. Majority of the respondents had neutral attitude to health and healthcare, and to self-perception; 94.03% and 73.63% respectively. From the results, there were significant association between distance and accessibility, and monthly income, plus between self-perception and demographic data (p<0.05). Self-perception was the most influencing factor as to why people were not able to seek treatment This can be used to educate the community regarding perceptions (khusnu or su’u dzan) and to the policy makers to ensure equal distribution of healthcare services throughout the country.